Venom diversity in the Neotropical scorpion genus Tityus: Implications for antivenom design emerging from molecular and immunochemical analyses across endemic areas of scorpionism - Borges, Adolfo (2020)
Scorpions of the Neotropical genus Tityus are responsible for most severe envenomations in the Caribbean, South America, and Lower Central America (LCA). Although Tityus is taxonomically complex, contains high toxin polymorphism, and produces variable clinical manifestations, treatment is limited to antivenoms produced against species with restricted distributions. In this study, we explored the compositional and antigenic diversity of Tityus venoms to provide improved guidelines for the use of available antivenoms at a broader geographic scale. We used immunoblotting, competitive ELISA, and in vivo studies to compare reactivity against commercial antivenoms from Brazil, Venezuela, and Mexico, as well as MALDI-TOF mass spectrometry, cDNA sequencing, and phylogenetic analyses to assess venom sodium channel-active toxin (NaTx) content from medically important Tityus populations inhabiting Brazil, Colombia, Costa Rica, Ecuador, Panama, Trinidad and Tobago, and Venezuela. Additionally, we raised rabbit antibodies against Tityus venoms from LCA to test for cross-reactivity with congeneric species. The results suggest that Tityus spp. possess high venom antigenic diversity, underlying the existence of four toxinological regions in Tropical America, based on venom composition and immunochemical criteria: LCA/Colombia/Amazonia (Region I), Venezuela (Region II), southeast South America (Region III), and a fourth region encompassing species related to toxinologically divergent Tityus cerroazul. Importantly, our molecular and cross-reactivity results highlight the need for new antivenoms against species inhabiting Region I, where scorpions may produce venoms that are not significantly reactive against available antivenoms